EVALUASI PEMBELAJARAN PENJASKES DI SMP NEGERI SE-KECAMATAN PRAYA - Lalu Hasan Ashari; Agus Nulhadi; Rodinal Musíd (Jurnal Ilmiah Global Education, 2023)
The purpose of this study was to find out how well the implementation of learning evaluation, especially the Physical Education learning in Public Junior High Schools in Praya District. The research model used is a survey technique using a questionnaire or questionnaire. Sources of information were obtained from 10 people from 6 public junior high schools in Praya District. Collecting data using a questionnaire or questionnaire. Data analysis using percentage descriptive analysis. Based on the results of the research, it can be concluded that the evaluation of learning in State Junior High Schools throughout the Praya District has been carried out very well with a percentage of 84.63%. The results of the research based on the implementation of the evaluation in each school obtained the result that the implementation of the evaluation at SMPN 5 Praya was the best SMPN in the process of implementing the Physical Education learning evaluation. SMPN 5 91.84% with very good category. The second is SMPN 1 Praya with a percentage of 90.38% in the very good category. The third is SMPN 4 Praya with a percentage of 89.18% in the very good category. The fourth is SMPN 2 Praya with a percentage of 85.50%. The fifth is SMPN 7 Praya with a percentage of 80.50% in the good category. And finally SMPN 3 with a percentage of 73.75% in the good category. So, on average, the evaluation process in Penjasorkes learning has been carried out very well.